Processing and hygrothermal effects on viscoelastic behavior of glass fiber/epoxy composites - Botelho, E. C.; Costa, M. L.; Pardini, L. C.; Rezende, M. C. (Springer, 2005)
Fiber reinforced epoxy composites are used in a wide variety of applications in the aerospace field. These materials have high specific moduli, high specific strength and their properties can be tailored to application requirements. In order to screening optimum materials behavior, the effects of external environments on the mechanical properties during usage must be clearly understood. The environmental action, such as high moisture concentration, high temperatures, corrosive fluids or ultraviolet radiation (UV), can affect the performance of advanced composites during service. These factors can limit the applications of composites by deteriorating the mechanical properties over a period of time. Properties determination is attributed to the chemical and/or physical damages caused in the polymer matrix, loss of adhesion of fiber/resin interface, and/or reduction of fiber strength and stiffness. The dynamic elastic properties are important characteristics of glass fiber reinforced composites (GRFC). They control the damping behavior of composite structures and are also an ideal tool for monitoring the development of GFRC's mechanical properties during their processing or service. One of the most used tests is the vibration damping. In this work, the measurement consisted of recording the vibration decay of a rectangular plate excited by a controlled mechanism to identify the elastic and damping properties of the material under test. The frequency amplitude were measured by accelerometers and calculated by using a digital method. The present studies have been performed to explore relations between the dynamic mechanical properties, damping test and the influence of high moisture concentration of glass fiber reinforced composites (plain weave). The results show that the E' decreased with the increase in the exposed time for glass fiber/epoxy composites specimens exposed at 80 degrees C and 90% RH. The E' values found were: 26.7, 26.7, 25.4, 24.7 and 24.7 GPa for 0, 15, 30, 45 and 60 days of exposure, respectively. (c) 2005 Springer Science + Business Media, Inc.